The Addition of Chitosan to GnRH Analog Induces Ovarian Resumption and Improves Conception Rates in Buffaloes - Y. A. Amin; A. Said (Tropical Animal Science Journal, 2021)
During hot season, female buffaloes suffer from ovarian inactivity due to hormonal insufficiency. Therefore, impaired reproductive efficiency causes low productivity of female buffaloes. The present study aimed to compare the effect of chitosan and/or insulin addition to GnRH analog during modified Ovsync program on ovarian response and pregnancy establishment in postpartum anestrous buffaloes during low breeding during the summer season. This study was carried out in buffaloes (N=135) suffering from ovarian inactivity during the summer season. The animals were divided into three treated equal groups, i.e., Group (1) basic Ovsync protocol, Group (2) insulin-sync protocol, and Group (3) chitosan-sync protocol. Blood samples were analyzed for progesterone, estradiol, and insulin concentrations before and after treatment. Follicular dynamics were studied through transrectal scanning of the ovaries. The results revealed that administration of insulin to GnRH analog (G2) significantly increased the diameter of the largest follicle and improved the conception rate compared to basic Ovsync protocol (G1). The addition of chitosan to GnRH analog (G3) caused a significant increase in the estrous induction rates (86.6%), increased the size of the largest follicle (p<0.05), and improved conception rates (76.9%) compared to basic Ovsync protocol (G1). Serum progesterone concentrations increased after treatment (p<0.05) in all groups indicating the resumption of ovarian activity. In addition, serum estradiol concentration increased after treatment in G2 and G3 (p<0.05) compared to G1. Therefore, we conclude that the addition of chitosan to GnRH analog induces ovarian resumption and improves conception rates. Subsequently, chitosan-sync protocol can be used in the treatment of the great infertility problem of postpartum anestrous during summer season in buffaloes. Furthermore, this protocol avoids the repeated injection of the animal as in insulin-sync protocol, so that protect the animal from more injection pains in addition to the decreases cost and duration of treatment.